FRACTURE SIMULATION ANALYSIS OF CONNECTING ROD ON DIESEL ENGINE - JIA DeWen; BAI JianYong; QIN Fei; FAN DeWen (Jixie qiangdu)
The connecting rod of high explosion pressure diesel engine was easily fatigue and fracture; the working dynamic load of connecting rod was obtained based on the multibody dynamics. And on this basis,the fatigue life danger zone was founded based on the dynamic stress recovery method,and fracture simulation was analyzed for the region. The results show that the operating cycles reduced from millions to ten thousand times after fatigue cracks taking place,so once the crack was founded,it was the best time to replace the connecting rod to avoid catastrophic accidents.